Tren Penelitian Konseling Post-Modern: Kajian Bibliometrik dari Tahun 2020–2025 - Shidqah, Syafira Badhiatus; Rahmawati, Alya; Aji, Oetari Zakiyah (TSAQOFAH, 2025)
This study aims to analyze the trends and characteristics of research on Solution-Focused Brief Therapy (SFBT) from 2020 to 2025 using a bibliometric and literature review approach. A total of 18 relevant articles were collected from the Google Scholar database and the Publish or Perish application, selected based on topic relevance, application context, and methodological completeness. The analysis focused on research methods, addressed issues, and the effectiveness of SFBT implementation. Bibliometric visualization using VOSviewer software identified three main thematic clusters interconnected by the central keyword "solution." The first cluster focuses on the implementation of SFBT in educational settings, the second highlights its use in individual counseling, and the third explores the integration of SFBT with religious approaches, such as Islamic counseling. Keyword density visualization further confirms the dominance of solution-oriented themes, along with the emergence of newer topics such as anxiety and self-development. These findings indicate that SFBT is a flexible and adaptive therapeutic approach with high relevance across educational, psychological, and cultural contexts. The implications of this study reinforce SFBT’s position as an evolving intervention model with strong potential for further development in interdisciplinary fields.